2006
DOI: 10.1097/01.jnen.0000235117.67558.6d
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Composition Differs Among Anatomically Diverse Malformations of Cortical Development

Abstract: Altered excitatory synaptic activity is likely a key factor in the neuronal hyperexcitability of developmental cerebral malformations. Using a combined morphologic and molecular approach, we investigated the NMDA receptor and related protein composition in human epileptic patients affected by periventricular nodular heterotopia, subcortical band heterotopia, or focal cortical dysplasia. Our results indicate that expression levels of specific NMDA receptor subunits are altered in both cerebral heterotopia and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
3
40
2
Order By: Relevance
“…Given that electrophysiological analysis of inhibitory synapses in these same animals, 15 including paired-pulse stimulation experiments, failed to reveal similar deficits we also believe these findings are specific to excitatory glutamatemediated synaptic transmission. Our findings are in contrast to studies in rodent malformation models 13,14,16 and human epileptic patients with heterotopia or focal cortical dysplasia 12,27,28 in which alterations in postsynaptic NMDA-type glutamate receptor subunit expression or function were reported. However, in a rodent model of polymicrogyria 20,29 and both the kainate and pilocarpine models of TLE, 18,19,30 a similar increase in EPSC frequency was observed, suggesting that enhanced excitatory drive may be a common feature of the epileptic brain.…”
Section: Discussioncontrasting
confidence: 86%
“…Given that electrophysiological analysis of inhibitory synapses in these same animals, 15 including paired-pulse stimulation experiments, failed to reveal similar deficits we also believe these findings are specific to excitatory glutamatemediated synaptic transmission. Our findings are in contrast to studies in rodent malformation models 13,14,16 and human epileptic patients with heterotopia or focal cortical dysplasia 12,27,28 in which alterations in postsynaptic NMDA-type glutamate receptor subunit expression or function were reported. However, in a rodent model of polymicrogyria 20,29 and both the kainate and pilocarpine models of TLE, 18,19,30 a similar increase in EPSC frequency was observed, suggesting that enhanced excitatory drive may be a common feature of the epileptic brain.…”
Section: Discussioncontrasting
confidence: 86%
“…Second, the increase in GAP-43 proteins could be modulated by NMDA receptor activation 34,35. Previous studies have demonstrated upregulation of the NMDA receptor complex in dysplastic neurons 23,27,28,36–38. Such hypothesis can be tested by immunostaining for both GAP-43 and NMDA receptors and the protein levels for both in relation to epilepsy duration in larger patient sample.…”
Section: Discussionmentioning
confidence: 94%
“…and GFAP, Molecular Probes; 1:2,000) or Alexa Fluor 488 GAM (for cytochrome-c, Molecular Probes; 1:2,000) were incubated with 10% normal goat serum and Triton 0.3% in PBS for 60 minutes and then overnight at 4°C with either the anti-cleaved caspase-3 or the anti phospho-c-Jun primary antibodies. The sections were then incubated for 2 hours with Alexa Fluor 488 or 546 GAR (Molecular Probes; diluted 1:2,000), repeatedly rinsed, and mounted as previously described (Finardi et al, 2006). For FJ/GFAP/caspase-3 triple labeling, sections were first immunoreacted with GFAP as previously described.…”
Section: Accepted Manuscriptmentioning
confidence: 99%